2005
DOI: 10.1007/s10290-005-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth Effects of Economic Integration: Evidence from the EU Member States

Abstract: Economic growth, economic integration, European Union, panel data,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 33 publications
(42 reference statements)
3
78
2
7
Order By: Relevance
“…Landau (1995) finds that there was no long-term growth effects associated with membership to the European Commission (EC). Badinger (2001) finds no permanent increase in growth rates related to economic integration within the European Union. Spilimbergo et al (1999) theoretically shows that RIAs could inhibit growth by changing the composition of trade in favour of low-technology goods or goods with less learning-by-doing.…”
Section: Background On Economic Integration In the Threementioning
confidence: 95%
“…Landau (1995) finds that there was no long-term growth effects associated with membership to the European Commission (EC). Badinger (2001) finds no permanent increase in growth rates related to economic integration within the European Union. Spilimbergo et al (1999) theoretically shows that RIAs could inhibit growth by changing the composition of trade in favour of low-technology goods or goods with less learning-by-doing.…”
Section: Background On Economic Integration In the Threementioning
confidence: 95%
“…Badinger (2001), examines the framework of the General Agreement on Tariffs and Trade (GATT)/WTO and membership in the European Free Trade Association (EFTA), among other economic characteristics of the European Union. De Benedictis and Tajoli (2011) show that being a member of the WTO makes a state more integrated into the international economy than non-member states.…”
Section: Economic Growth Through Economic Integrationmentioning
confidence: 99%
“…For example, Badinger (2005) found that European economic integration has had a sizeable impact on the level of income but has not had a permanent effect on the rate of growth. This is in line with recent investigations of the impact of trade liberalizations using difference-in-differences approaches (Estevadeordal and Taylor, 2013) but goes against the hopeful predictions of some economists in the 1980s.…”
Section: What Did 1980s' Economists and Policymakers Get Right Omentioning
confidence: 99%